Causality of ICT Expenditure on Financial Performance in Indonesia’s Logistics and Courier Sector, 2020–2024 - Imma Ismaniar; Muhammad Fikry Januar; Dede Ibrahim Maulana; Solihin; Eko Prasetyo; Astri Julianari (Journal of Applied Digital Business Management, 2026)
ICT investment has emerged as a strategic imperative for Indonesia’s logistics sector, propelled by e-commerce acceleration and post-pandemic demands for operational efficiency. This study analyzes the causal relationship and potential "lag effect" between ICT expenditure and financial performance (Return on Assets - ROA) among six public logistics firms on the Indonesia Stock Exchange from 2020 to 2024. Utilizing Panel Vector Autoregression (PVAR) and Granger causality tests, the research identifies a unidirectional relationship where ICT spending significantly influences ROA, though the reverse is not true. Impulse response analysis confirms a lag effect, revealing that the positive impact of ICT on profitability optimizes after a delayed period, averaging two years. Despite fluctuating financial growth amid global economic uncertainty, these findings challenge the Solow Paradox by demonstrating that ICT serves as a long-term profitability driver. The delayed ROA improvement suggests that ICT’s strategic value stems from deep business process transformation rather than immediate operational cost increases. Ultimately, this underscores the necessity for management to view ICT not as a mere expense, but as a sustainable strategic investment essential for achieving tangible long-term financial gains. Keywords: Financial Performance (ROA); Granger Causality; ICT Expenditure; Lag Effect, Logistics.